La libération de la caution par la faute du créancier - Poudrier-LeBel, Louise (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
Since the decision of the Supreme Court in Soucisse, a growing number of sureties try to obtain their liberation by invoking a fault of the creditor. This phenomenon occurs in the province of Quebec as in the other provinces of Canada. This paper relates mostly to the Quebec Law. The sureties plead a fault in information about the nature or the consequences of their contract or about the risks and circumstances of the operation. The author writes that such a general duty of information does not exist, except if the creditor has been contractually engaged to do so. Nevertheless, if the creditor gives wrong information with bad faith, he will be held liable. Secondly, the sureties invoke the recall of the loan. Here again, there is no fault on the creditor's part, if the term is arrived or if a reasonable notice has been given when the debt is payable on demand. But if the creditor has promised that he would not recall his loan for a certain period, he must do so. Thirdly, the sureties invoke a fault in the realization of the securities for a low price. The courts will ascertain whether the sale has been held in accordance with prescriptions of the law for this type of security. If the creditor sells privatly, the courts do not hold him liable if the price obtained is justified within the economic context. In case of a fault in the realization of the securities, an action on liability belongs to the principal, the company, and not to the surety, the shareholder, a victim by ricochet, except if the goods are his own. Nevertheless if the surety is sued, he may oppose a fin denon-recevoir. The burden of the proof of the fault will be more or less easy according to the circumstances of the case. Most often, an exoneration clause will deny liability except in the case of bad faith. In the absence of such a clause, the criterium is that of a reasonable man. Sureties must also prove the amount of the prejudice. Recent amendments to the Bank Act and to the Act respecting Bills of lading, Receipts and Transferts of property in stock impose new standards of conduct on the creditor and will offer more protection to sureties.